2004
DOI: 10.1088/0031-9155/49/22/012
|View full text |Cite
|
Sign up to set email alerts
|

RF dosimetry: a comparison between power absorption of female and male numerical models from 0.1 to 4 GHz

Abstract: Realistic numerical models of human subjects and their surrounding environment represent the basic points of radiofrequency (RF) electromagnetic dosimetry. This also involves differentiating the human models in men and women, possibly with different body shapes and postures. In this context, the aims of this paper are, firstly, to propose a female dielectric anatomical model (fDAM) and, secondly, to compare the power absorption distributions of a male and a female model from 0.1 to 4 GHz. For realizing the fDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…To obtain accurate results on real situations, very high resolution models of the human body should be implemented for different ages, dimensions and phenotypes. For instance, an increase of whole-body SAR up to 25% has been reported for female models (compared to male ones), due to different content and distribution of fat tissue [31]. Such models should be also able to represent typical complex postures; whereas the ones available now represent the posture during MRI or a computed axial tomography (CAT) scan.…”
Section: Numerical Dosimetrymentioning
confidence: 99%
“…To obtain accurate results on real situations, very high resolution models of the human body should be implemented for different ages, dimensions and phenotypes. For instance, an increase of whole-body SAR up to 25% has been reported for female models (compared to male ones), due to different content and distribution of fat tissue [31]. Such models should be also able to represent typical complex postures; whereas the ones available now represent the posture during MRI or a computed axial tomography (CAT) scan.…”
Section: Numerical Dosimetrymentioning
confidence: 99%
“…5 and 8 that the magnitudes of temperature rise of the male subjects were comparatively lower than that of the female subjects in both the cases. Using numerical simulations on suitable female and male dielectric anatomic models, Sandrini et al [38] have shown that near head and neck regions, the absorption at 1000 MHz does not substantially differ with gender as variations in sub-cutaneous fat levels are insignificant in these regions. Based on the above finding it can be stated that the variation in the temperature rise in the male and female subjects can be due to variation of specific heat of the tissues as the water content in male tissue is higher compared to that in female tissues (58.3 ± 6.7% in males compared to 48.5 ± 8.6% in females) [39].…”
Section: Resultsmentioning
confidence: 99%
“…This model is very accurate and considerably complete and complex, but has yet to be use for studies pertaining to passive RFID systems in dense environments. Sandrini et al [5] published a method that is resource friendly, which completely ignored the use of voxels. This method disregarded the voxel method and allows for data extraction from grayscales in the MRI data, which provide for semi-automatic generation of the dielectric model [1,5].…”
Section: Related Workmentioning
confidence: 99%
“…Sandrini et al [5] published a method that is resource friendly, which completely ignored the use of voxels. This method disregarded the voxel method and allows for data extraction from grayscales in the MRI data, which provide for semi-automatic generation of the dielectric model [1,5]. The results of this experiment depicted in Figure 1c show that a dielectric anatomical model can be used to generalize the exposure to RF radiation from the far field [1,5].…”
Section: Related Workmentioning
confidence: 99%